Transforming maritime education through a competency-based framework for marine engineering technicians - R. Riyanto; Brenhard Mangatur Tampubolon; Susi Herawati (Universitas Muhammadiyah Malang, 2025)
This study addresses the urgent need for marine engineering technicians equipped with the competencies required to navigate the rapidly evolving demands of the maritime industry. As technologies such as artificial intelligence (AI), robotics, and green propulsion systems become integral to maritime operations, educational institutions must adopt competency-based frameworks that align with real-world industry expectations. While prior research has examined maritime education broadly, few studies have directly linked educational competencies to current and emerging industry needs. This research aimed to identify the core competencies essential for marine engineering technicians and to develop a competency-based framework to strengthen educational outcomes. A qualitative approach was employed, utilizing semi-structured interviews with maritime professionals, educators, and industry experts, alongside observations of existing training practices. Findings indicate that the proposed framework effectively addresses both conventional and emerging technical skills, though challenges remain in enhancing industry collaboration and upgrading technological infrastructure. The study concludes that a well-integrated competency-based framework can significantly improve the relevance, adaptability, and quality of marine engineering education, preparing technicians to meet both present and future maritime challenges.